Obstacles to ISO 9001 certification in SMEs. (2nd October 2020) - Sfakianaki, Eleni; Kakouris, Andreas P.
Abstract : Several studies have analysed obstacles to ISO 9001 certification, however there remains a clear need for empirical research, particularly for small-to-medium enterprises (SMEs). This paper explores the obstacles to ISO 9001 certification for SMEs in the Greek food and beverage (F&B) industry. This study was done using a qualitative approach, appraising case studies to investigate in depth how companies perceived the ISO 9001 certification process. Four organisations were examined using in-depth interviews with top and middle managers from these companies. The findings showed that, although they successfully implemented ISO 9001, certified companies in the F&B industry faced a number of obstacles. The most commonly cited of these were bureaucracy, lack of guidance by top management, demands on time and resources and reaction from employees. However, research also threw light onto other drawbacks that are rarely discussed. Interestingly, the obstacles observed in the four companies examined differed somewhat, and they were not perceived in each company with the same intensity. This study may enhance existing knowledge of SMEs and provide useful insight to managers and company owners wishing to pursue ISO 9001 certification and needing assistance in preparing for certification. Using these data, researchers can further their knowledge and acknowledge drawbacks.